USAHA TENUN IKAT DI DESA TIWURANA KECAMATAN INERIE KABUPATEN NGADA - Meo, Maria Eflida A.; Samin, Mikael; Manek, Agustinus Hale (Universitas Nusa Cendana, 2023)
This study aims to: (1) identify the supporting and inhibiting geographical components of the tie-woven business in Tiwurana Village, (2) find out the production process of the tie-woven business in Tiwurana Village and (3) find out the contribution of the results of the tie-woven business in Tiwurana Village. The method used in this research is descriptive quantitative. Sources of data in this study include primary and secondary data obtained through interviews, observation and documentation study. Respondents in the study were woven craftsmen with a population of 20 woven craftsmen and the sample used a non-probability sampling technique with all populations as samples. Quantitative descriptive data analysis used frequency tables. The results of this study are: (1) in the form of geographic components supporting the woven textile business; the physical environment (soil and climate), the human environment (labor) and the accessibility of the local area, (2) the geographical components that inhibit the woven textile business; human environment (lack of capital, labor, lack of marketing breadth) physical environment in the form of climate change, (3) the production process of woven weaving learns various stages. such as the arrangement of threads for making motifs, coloring, washing, drying, arranging threads after drying, weaving and using non-natural factory raw materials because they are difficult to obtain, (4) the contribution of the results of woven fabrics; these products are sold in the market to meet daily needs, in addition to that as the inheritance of traditional culture during marriage death